Design and Development of Metoprolol Succinate Dual-Phase Extended-Release Tablets - Ranka, Saloni; Jain, Vikas; Gehlot, Narendra; Malviya, Yogendra (Journal of Neonatal Surgery, 2025)
This study presents comprehensive preformulation, precompression, and postcompression evaluations for the development of dual-phase extended-release tablets of Metoprolol Succinate (MTS). Preformulation studies confirmed the identity and purity of MTS through organoleptic assessment, melting point analysis, and FTIR spectroscopy, which validated the presence of characteristic functional groups and demonstrated compatibility with key excipients including MCC PH101, HPMC K4M, PVP K30, sodium stearyl fumarate, and colloidal silicon dioxide. UV spectrophotometric analysis established a λmax of 240 nm, and calibration curves in 0.1 N HCl and phosphate buffer pH 6.8 exhibited excellent linearity (R² ≈ 0.99). Solubility studies revealed high solubility in water, 0.1 N HCl, and methanol, with moderate solubility in PBS pH 6.8, indicating favorable dissolution across physiological pH conditions. Precompression studies of immediate-release (IR1–IR3) and sustained-release (F1–F6) blends demonstrated acceptable flow and compressibility, with all formulations exhibiting suitable micromeritic properties for direct compression. Postcompression evaluations confirmed compliance with pharmacopoeial standards, as tablets exhibited adequate hardness, friability below 1%, acceptable weight variation, uniform thickness, and drug content ranging from 98.23% to 99.52%. In vitro dissolution studies showed that drug release was strongly influenced by polymer viscosity, with HPMC K4M–based formulations (F1–F3) providing more sustained release than Eudragit L100–based formulations (F4–F6). Among the formulations, F3 (containing 20 mg HPMC K4M) demonstrated the most controlled release over 12 hours. Stability studies of F3 confirmed no significant changes in tablet quality under accelerated conditions (40 ± 2°C/75 ± 5% RH) for three months. Overall, the findings support the successful development of a stable and effective dual-phase extended-release tablet of Metoprolol Succinate suitable for sustained therapeutic action